Study of the Long Non-Coding RNA C/EBPβ-AS in Cutaneous Melanoma - Fernandes, Rita Valador (2017)
Cutaneous malignant melanoma (CMM) is the ninth most common cancer type in more developed regions. Despite comprehending less than 5% of all skin cancer cases, CMM stands as the most lethal skin neoplasm, with a detectable increase in incidence throughout recent decades. While the B-rapidly accelerated fibrosarcoma (BRAF) inhibitor vemurafenib appears to be effective in ~80% of CMM patients carrying the BRAFV600E mutation, the vast majority of patients becomes resistant to treatment. Given that, it is imperative to seek new therapeutic strategies. Long non-coding RNAs (lncRNAs) are a functionally diverse class of transcripts that lack an evident protein-coding function and have over 200 nucleotides of length. The advent of growing sensitivity of RNA sequencing methods, as well as computational prediction techniques is enabling the increasing identification of such RNA transcripts. Among the few that have been functionally characterized, several have been linked to numerous aspects of carcinogenesis, with an evident role in gene expression regulation. CCAAT/Enhancer-Binding Protein β (C/EBPβ) is a transcription factor implicated in many fundamental cellular processes, including cellular senescence and proliferation. CCAAT/Enhancer-Binding Protein β Antisense (C/EBPβ-AS) is an antisense lncRNA transcribed from the reverse strand of C/EBPβ, with a genomic 5’ overlap with C/EBPβ gene, which has not previously been studied. Here we characterize biologically relevant features of C/EBPβ-AS and propose a role for C/EBPβ-AS in epigenetic regulation of C/EBPβ expression in melanoma cell lines. Moreover, we show that modulation of C/EBPβ-AS expression resensitizes vemurafenib-resistant melanoma cells to vemurafenib. Finally, we investigate the impact of modulation of C/EBPβ-AS expression in MAPK/ERK and PI3K/AKT pathways, both commonly found to be dysregulated in CMM. Taken together, our research provides new insights on an antisense lncRNA-mediated mechanism of gene regulation, with implications on CMM targeted-therapy resistance.